The role of intermediate demand and technology for international competitiveness of the KIBS sector: evidence from European Union countries. Issue 7 (3rd October 2017) - Wyszkowska-Kuna, Joanna
ABSTRACT: In this paper, it is tested whether intermediate consumption of knowledge-intensive business services (KIBS) in the economy and technology advancement in the KIBS sector (measured by R&D expenditures) affect the international competitiveness of a country's KIBS sector. First, the definition of KIBS trade, in light of the available data from the balance of payments statistics, is presented. Then, using a panel data set from the EU countries over the period 2000–2009, a panel cointegration approach to estimating the model is adopted. The empirical study shows that among the old EU countries only those with high income are competitive in KIBS exports. Estimation results demonstrate that their competitiveness in KIBS exports is positively determined by domestic and imported KIBS intensity in the economy, as well as by the KIBS sector's technology advancement. The new EU countries usually were not competitive in KIBS exports, and those which were successful in this field seem to have derived their success mainly from international outsourcing rather than from building their own capacities. Their competitiveness in KIBS exports was positively determined by the KIBS sector's endowment in human capital, or via domestic KIBS intensity in the economy together with lower labour costs.